A systematic review of children’s participation in child protection decision‐making: Tokenistic presence or not? - Toros, Karmen (Children & society, 2021)
This article examines children's views on and experiences with participation in the child protection system's decision‐making process. The systematic review follows the PRISMA statement and includes 12 peer‐reviewed articles published in academic journals from 2006 to 2017. Findings suggest that children's contact with their worker was limited or non‐existent, which minimised opportunities to express views regarding their situation; child–worker contacts lacked dialogue, information about the process of intervention and trusting relationships, meaning that without a voice, children were not engaged in making decisions. Although data are limited, they suggest little or no dialogue with children by child protection workers. Furthermore, children voiced their experiences of not being informed of or understanding the process or decisions made about their lives.